PENGARUH MANAJEMEN LABA MENJELANG INITIAL PUBLIC OFFERING PADA RETURN SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Wicitra, Gede Bandem; Wirasedana, Wayan Pradnyantha (E-Jurnal Akuntansi, 2016)
The aim of this study was to determine earnings management during the eve of the company's Initial Public Offering. The study also examined the effect of earnings management on stock returns and firm size as moderating the relationship between earnings management and stock returns. The sample was a company that did an IPO in 2010-2014 as many as 60 companies after purposive sampling. The data analysis technique used is the interaction is often called the moderated regression analysis. Modified Jones Model is used to detect the earnings management conducted. Cumulative abnormal return is used as a proxy of the stock return. This study provides evidence that the company's earning management of one year and two years before the IPO a positive effect on stock returns. The study also proved that the size of the company can strengthen the positive effect of earnings management on stock returns.
Keywords: IPO, earning management, stock returns, company size